2017
DOI: 10.1155/2017/5125980
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Long-Term Chaetomellic Acid A Administration on Renal Function and Oxidative Stress in a Rat Model of Renal Mass Reduction

Abstract: Purpose. This study aimed to evaluate the effect of chronic treatment with chaetomellic acid A (CAA) on oxidative stress and renal function in a model of renal mass reduction. Methods. Male Wistar rats were subjected to 5/6 nephrectomy (RMR) or sham-operated (SO). One week after surgery, rats have been divided into four experimental groups: RMR: RMR rats without treatment (n = 14); RMR + CAA: RMR rats treated with CAA (n = 13); SO: SO rats without treatment (n = 13); and SO + CAA: SO rats treated with CAA (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…According to Qian et al [33], CAA has a reduced off-target toxicity relative to others farnesyltransferase inhibitors. In fact, as we have previously discussed [25], we did not observe adverse effects after the administration of CAA to rats. However, possibly chronic administration of CAA (0.23 µg/Kg three times a week) may have some toxicity in rats with CKD, while in healthy animals, administration of CAA is innocuous.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…According to Qian et al [33], CAA has a reduced off-target toxicity relative to others farnesyltransferase inhibitors. In fact, as we have previously discussed [25], we did not observe adverse effects after the administration of CAA to rats. However, possibly chronic administration of CAA (0.23 µg/Kg three times a week) may have some toxicity in rats with CKD, while in healthy animals, administration of CAA is innocuous.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, CAA administration in rats, after brain damage induced by an excitotoxic stimulus, significantly reduced superoxide production [19]. Also, an in our previous study [25], we have observed that CAA attenuate 5/6 RMR-induced oxidative stress in rats. Oxidative stress plays an important role in renal injury induced by 5/6 RMR [62,63].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations